Overexpression of miR-124 enhances the therapeutic benefit of TMZ treatment in the orthotopic GBM mice model by inhibition of DNA damage repair - Yuchen Wei; Peng Wang; Jianhui Zhao; Xin Fan; Jun Jiang; Xiuli Mu; Yuzhou Wang; Angang Yang; Rui Zhang; Shijie Hu; Zhangyan Guo (Cell Death and Disease)
Abstract Glioblastoma (GBM) is the most common malignant primary brain cancer with poor prognosis due to the resistant to current treatments, including the first-line drug temozolomide (TMZ). Accordingly, it is urgent to clarify the mechanism of chemotherapeutic resistance to improve the survival rate of patients. In the present study, by integrating comprehensive non-coding RNA-seq data from multiple cohorts of GBM patients, we identified that a series of miRNAs are frequently downregulated in GBM patients compared with the control samples. Among them, a high level of miR-124 is closely associated with a favorable survival rate in the clinical patients. In the phenotype experiment, we demonstrated that miR-124 overexpression increases responsiveness of GBM cells to TMZ-induced cell death, and vice versa. In the mechanistic study, we for the first time identified that RAD51, a key functional molecule in DNA damage repair, is a novel and bona fide target of miR-124 in GBM cells. Given that other miR-124-regulated mechanisms on TMZ sensitivity have been reported, we performed recue experiment to demonstrate that RAD51 is essential for miR-124-mediated sensitivity to TMZ in GBM cells. More importantly, our in vivo functional experiment showed that combinational utilization of miR-124 overexpression and TMZ presents a synergetic therapeutic benefit in the orthotopic GBM mice model. Taken together, we rationally explained a novel and important mechanism of the miR-124-mediated high sensitivity to TMZ-induced cell death in GBM and provided evidence to support that miR-124-RAD51 regulatory axis could be a promising candidate in the comprehensive treatment with TMZ in GBM.